Biochemical properties of crude extracellular proteases from Chromohalobacter salexigens BKL5 and Micrococcus luteus 11A - Ayu Ashari Achmad; M. Saifur Rohman; Irfan D. Prijambada (Universitas Gadjah Mada, 2016)
In this work, we have reported an enzymatic activity and biochemical properties of extracellular proteases from Chromohalobacter salexigens BKL5 and Micrococcus luteus 11A. C. salexigens BKL5 and M. luteus 11A were previously isolated from Bledug Kuwu mud volcano and dietary industry wastewater treatment, respectively. Both bacterial strains were able to produce extracellular proteases, when grown on minimal agar medium supplemented with 1% of skim milk. Proteolytic indexes of C. salexigens BKL5 and M. luteus 11A were 2.5±0.14 and 2.9±0.42, respectively. Both extracellular proteases exhibited optimum enzymatic activity at pH 7, with specific activity of C. salexigens BKL5 was 13.3% higher than that of M. luteus 11A. Optimum temperature for enzymatic activity of both proteases was 45°C. Metal cofactor preferences assay showed that extracellular protease from C. salexigens BKL5 preferred Zn2+, meanwhile extracellular protease from M. luteus 11A mainly preferred Ca2+ ion. Metal cofactor preferences assay also suggested that crude extracellular protease from C. salexigens BKL5 was categorized as metalloprotease, meanwhile crude extracellular protease of M. luteus 11A was common neutral protease. The enzymatic stability assay against various salt concentrations showed that crude extracellular protease from C. salexigens BKL5 was more stable than that of M. luteus 11A.